Effects of forest spatial types, element compositions and forest stands on restorative potential and aesthetic preference - Wang, Yuqian; Liu, Geyan; Jiang, Mingyan; Yang, Qin; Chen, Qibing; Li, Xi; Luo, Zhenghua; Song, Huixing; Du, Juan; Yu, Xiaofang; Lv, Bingyang; Li, Nian (Frontiers in Forests and Global Change, 2023)
Introduction As global urbanization intensifies, the physical and mental stressors of modern life have led to the growing prevalence of suboptimal health conditions. Spending time in a forest benefits human health and well-being. In this context, based on the forest spatial types (forest interior and forest edge spaces), landscape elements (architecture, water and roads) and forest stands (coniferous, broadleaf and bamboo forests), this study investigated the effects of different forest spatial landscape characteristics on the restorative potential for college students, aesthetic preference and eye movement behavior (total fixation duration and fixation count). Methods In this study, a total of 60 subjects were exposed to 42 photographs depicting typical forest landscapes acquired through field studies. The Short-version Revised Restoration and Preference Scale and eye-tracking technology, were employed to study the recovery efficiency and visual attraction of forest spatial of different forest spatial types, element compositions and forest stands. Results (1) The restorative potential and aesthetic preference score of forest edge spaces were significantly higher than those of forest interior spaces. (2) The restorative potential of bamboo forests was significantly higher than those of coniferous and broadleaf forests. (3) In terms of forest interior space, the restorative potential of “forest + 1 element” composition and “forest + 2 elements” composition was significantly higher than that of pure forest, and the restorative potential of interior space of bamboo forest was significantly higher than those of coniferous and broadleaf forests. (4) In terms of forest edge space, the restorative potential of “forest + 2 elements” composition was significantly higher than that of pure forest, and the restorative potential of pure forests was significantly higher than that of the “forest + 1 element” composition. (5) The restorative potential of forest spatial landscape characteristics positively correlated with aesthetic preference and negatively correlated with total fixation duration and fixation count. These results can provide a reference for future forest landscape research, construction and management.